Kontribusi Pemangku Kepentingan Dana Zakat, Infak, Sedekah dan Wakaf Dalam Penanggulangan COVID-19: Contribution of Stakeholders of Zakat, Infaq, Sedekah and Waqf Funds In Tackling COVID-19 - iqbal fadli muhammad iqbal (Direktorat Jenderal Bimbingan Masyarakat Islam, 2021)
This study attempts to analyze Contribution of Stakeholders of Zakat, Infak, Sedekah and Waqf Funds In Tackling COVID-19. This is because the lack of publication related the contribution of any stakeholders such as the ministry of religious affairs, Badan Amil Zakat Nasional (BAZNAS), Lembaga Amil Zakat, Badan Wakaf Indonesia (BWI) dan Nazir. The methodology that is used by the combination of interview, discusion, literasi study, and survey respondents for penyelenggara zakat dan wakaf serta penyuluh agama Islam sector zakat dan wakaf. The research results show that the contribution of stakeholders ziswaf funds had played an adequate role important. The results of the study show that accumulatively collected funds for the prevention of Covid-19, for zakat, infaq, sedekah and other religious social funds reached 392,5 billion. Meanwhile, the stimulus for assistance from the Ministry of Religion as the contribution of zakat and waqf in the fight against Covid-19 reached 25.7 billion. As for the cash waqf for the prevention of Covid-19, it reached 81 billion. The results of this study also illustrate the role of waqf assets managed by several nazir for the prevention of Covid-19 with a total of 119 hospitals, and ventilator waqf. Suggestions for further research are to expand reference sources and information on contributions from ZISWAF funds.